2020
DOI: 10.1049/iet-ipr.2020.1119
|View full text |Cite
|
Sign up to set email alerts
|

MaskHunter: real‐time object detection of face masks during the COVID‐19 pandemic

Abstract: Due to the COVID-19 pandemic at present, it is necessary to detect whether pedestrians in public places wear face masks or not for preventing the spread of novel coronavirus. The pedestrian flow in public places is large, and it puts forward higher requirements for the accuracy and speed of real-time mask detection. Improving the face mask detection effect especially in the night environment is a challenging problem. A novel object detector namely MaskHunter is proposed in this study for the real-time mask det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The evolution from GIoU to CIoU makes the regression loss more accurate and the target frame regression more stable. However, it is found that the above three types of loss functions will cause the problem of an inaccurate positioning frame for targets with a high aspect ratio and dense targets; in order to solve this problem, the pixel IoU (PIoU) function [27] is introduced.…”
Section: Loss Function Improvedmentioning
confidence: 99%
“…The evolution from GIoU to CIoU makes the regression loss more accurate and the target frame regression more stable. However, it is found that the above three types of loss functions will cause the problem of an inaccurate positioning frame for targets with a high aspect ratio and dense targets; in order to solve this problem, the pixel IoU (PIoU) function [27] is introduced.…”
Section: Loss Function Improvedmentioning
confidence: 99%
“…While the previously mentioned studies tackle the face mask recognition problem as a classification task, object detection based approaches utilize You Only Look Once (YOLO) approaches also report 94% and 81% average precision [3,28].…”
Section: Face Mask Recognitionmentioning
confidence: 99%
“…Countries enforced strict laws and regulations to reduce the transmission of the virus and prevent its spread [2], especially following the lift of the nationwide lockdown. For instance, some counties have made wearing face masks in public mandatory [3,4], including the United Arab Emir-ates (UAE), as it is an efficient way to limit the spread of the virus [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Their data augmentation methodology involves filtering images through greyscale and Gaussian blurring. In [5], the authors utilize YOLOv4 to detect whether pedestrians adhere to the rules of face mask wearing or not, especially at night time. Alok et al [16] proposed CNN and VGG16 model to detect people not wearing a mask.…”
Section: Introductionmentioning
confidence: 99%